A Review of Impaired Neuroplasticity in Schizophrenia Investigated with Non-invasive Brain Stimulation - Bhandari, Apoorva; Voineskos, Daphne; Daskalakis, Zafiris J.; Rajji, Tarek K.; Blumberger, Daniel M. (Frontiers in Psychiatry, 2016)
Background: Several lines of evidence implicate dysfunctional neuronal plasticity in the pathophysiology of schizophrenia. Aberrant glutamatergic and gamma amino-butyric acid neurotransmission are thought to underlie core cognitive deficits and negative symptoms of schizophrenia. Non-invasive brain stimulation (NIBS) allows for the in-vivo study of cortical plasticity and excitability at the systems level of the human motor cortex. This review will focus on summarizing the available neurophysiological evidence for impaired motor cortical plasticity in schizophrenia assessed by NIBS. Methods: A search of MEDLINE, Embase and PubMed on the use of NIBS techniques to investigate neuroplasticity in the motor cortex of schizophrenia patients was performed. The relevant articles were summarized. Conclusions: Our review of the literature reveals evidence for disrupted neuroplasticity in schizophrenia and its close association to alterations in cortical inhibition and dysfunctional intracortical connectivity. Further investigations are required to elucidate the neurobiological mechanisms that underlie dysfunctional plasticity in schizophrenia in order to develop more targeted therapeutic interventions for schizophrenia patients.